Association of serum levels of laminin, type IV collagen, procollagen III N-terminal peptide, and hyaluronic acid with the progression of interstitial lung disease. Issue 18 (May 2017) - Su, Yiliang; Gu, Hongyan; Weng, Dong; Zhou, Ying; Li, Qiuhong; Zhang, Fen; Zhang, Yuan; Shen, Li; Hu, Yang; Li, Huiping
Abstract : Abstract: Noninvasive and convenient tests to assess pulmonary fibrosis and disease progression in interstitial lung diseases (ILDs) are currently unavailable. The extracellular matrix molecules, laminin (LN), type IV collagen (IVC), procollagen III N-terminal peptide (PIIINP), and hyaluronic acid (HA) are involved in ILD development and progression. This study aims to investigate the association of disease progression and serum levels of LN, IVC, PIIINP, and HA in patients with ILD. This retrospective study included 323 patients (162 cases of idiopathic pulmonary fibrosis [IPF] and 161 cases of connective tissue diseases ILD [CTD-ILD]) treated in Shanghai Pulmonary Hospital between January 2013 and January 2015 and 160 healthy controls. Serum LN, IVC, PIIINP, and HA were analyzed by radioimmunoassay. Data of the percentage of forced vital capacity in the prediction value (FVC%pred), the percentage of diffusing capacity of the lung for carbon monoxide in the prediction value (DLCO%pred), high resolution computed tomography (HRCT) score, and patient mortality were collected. Serum LN, IVC, PIIINP, and HA were significantly increased in the patients with IPF or CTD-ILD compared with the healthy controls (all P < .05) and were further elevated in the acute exacerbation cases (all P < .05). Serum LN, IVC, PIIINP, and HA positively correlated with HRCT score and negatively correlated with FVC%pred and DLCO%pred significantly in the patients (all P < .05). The survived patients had significantly lower serum LN, IVC, PIIINP, and HA than the dead patients (all P < .05). Serum levels of LN, IVC, PIIINP, and HA may reflect ILD progression and may be indicators for the severity of ILDs.